Effect of Ultrasonic on Crystallinity of Nano-Hydroxyapatite viaWet Chemical Method: Crystallination of nano-hydroxyapatite - Sahebali Manafi,; Seyyed Hossein Badiee, (Iranian Journal of Pharmaceutical Sciences, 2008)
IranAbstractIn a hydrothermal route devoted for synthesis of Ca10(PO4)6(OH)2 (HA) nanostructures, morphology can be controlled by experimental condition to form magical HAor nanostructured nanoparticles. In an intermediate condition, a novel nanostructure namely rose-like bundle of HArod-likes was found, which is different from known HAnanostructures. The chemical synthesis of nanopowders under hydrothermal process provides an opportunity to control the HAand is dependent on sonochemical process. Since the procedure is very simple, this method is of general interest, and can be used for similar syntheses. The phase purity of the as-prepared products was determined by X-ray diffraction (XRD), fourier transform infrared (FT-IR), and scanning electron microscopy was applied to investigate the morphology.The microstructure of the HAproducts was further observed by transmission electron microscopy and energy-dispersive X-ray spectroscopy. The chemical composition of the as-synthesized powder was analyzed by inductively coupled plasma atomic emission spectroscopy. Interestingly, the approach proposed can be used for the preparation of different nanostructures of HA.